Direct evidence for the atovaquone action on the Plasmodium cytochrome bc1 complex. Issue 3 (June 2015) - Siregar, Josephine E.; Kurisu, Genji; Kobayashi, Tamaki; Matsuzaki, Motomichi; Sakamoto, Kimitoshi; Mi-ichi, Fumika; Watanabe, Yoh-ichi; Hirai, Makoto; Matsuoka, Hiroyuki; Syafruddin, Din; Marzuki, Sangkot; Kita, Kiyoshi
Abstract: Atovaquone, a coenzyme Q analogue has been indicated to specifically target the cytochrome bc 1 complex of the mitochondrial respiratory chain in the malarial parasite and other protozoan. Various mutations in the quinone binding site of the cytochrome b gene of Plasmodium spp. such as M133I, L144S, L271V, K272R, Y268C, Y268S, Y268N, and V284F are suggesting to associate with resistance to atovaquone. There is no direct evidence of relation between the mutations and resistance to atovaquone in Plasmodium parasite that has been available. Technical difficulties in isolating active assayable mitochondria in the malarial parasite hinder us to obtain direct biochemical evidence to support the relation between the mutations and drug resistance. The establishment of a mitochondrial isolation method for the malaria parasite has allowed us to test the degree of resistance of Plasmodium berghei isolates to atovaquone directly. We have tested the activity of dihydroorotate (DHO)-cytochrome c reductase in various P. berghei atovaquone resistant clones in the presence of a wide concentration range of atovaquone. Our results show the IC50 of P. berghei atovaquone resistant clones is much higher (1.5 up to 40 nM) in comparison to the atovaquone sensitive clones (0.132–0.465 nM). The highest IC50 was revealed in clones carrying Y268C and Y268N mutations (which play an important role in atovaquone resistance in Plasmodium falciparum ), with an approximately 100-fold increase. The findings indicate the importance of the mutation in the quinone binding site of the cytochrome b gene and that provide a direct evidence for the atovaquone inhibitory mechanism in the cytochrome bc 1 complex of the parasite. Graphical abstract: Highlights: Mutations of cytb gene of Plasmodium spp. are thought to be for atovaquone resistance. The activity of dihydroorotate-cytochrome c reductase in P. berghei resistant clones was tested. The IC50 of the resistant clones was 1.5 up to 40 nM. The IC50 of the sensitive clones was 0.132 to 0.465 nM. The quinone binding (Qo ) site in the cytochrome bc 1 complex is the atovaquone action site.